Clinical Efficacy and Prognosis Study of Recurrent Laryngeal Nerve Anatomical Surgery on serum TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β and outcomes: serum TNF-α, CRP, IL-6, IL-10, and IL-1β in Thyroidectomy - Cheng, Hui (Journal of Medical Biochemistry, 2025)
Introduction: This study aimed to evaluate the effects of recurrent laryngeal nerve anatomical exposure during thyroidectomy on serum TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β, treatment outcomes, complications, and patient prognosis, with a specific focus on inflammatory and stress markers, including interleukins. Methods: A total of 110 patients with thyroid lesions undergoing thyroidectomy were randomly assigned to two groups: Expose (n=55), where the recurrent laryngeal nerve was exposed during surgery, and non-expose (n=55), where it was not. Various outcome measures were assessed, including surgical efficacy, vocal cord function, serum inflammatory and stress markers (TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β), thyroid function changes, postoperative complications (including RLNI), and patient satisfaction. Additionally, quality of life (QoL) was evaluated. Results: The Expose group exhibited a smaller flap area and shorter hospital stays compared to the non-expose group, though the surgery took longer (P<0.05). On postoperative day 30, patients in the Expose group showed lower values of fundamental frequency, jitter, and shimmer in vocal cords, indicating improved vocal function (P<0.05). Furthermore, the Expose group had significantly higher QoL scores and a lower incidence of RLNI (3.64% vs. 20.00%, P<0.05), with improved surgical satisfaction (96.36% vs. 76.36%, P<0.05). Notably, the Expose group exhibited reduced levels of inflammatory and stress markers, including lower TNF-α, CRP, IL-6, and IL-1β, and higher IL-10, which correlated with reduced postoperative pain and inflammation. Conclusion: Anatomical exposure of the recurrent laryngeal nerve during thyroidectomy enhances postoperative recovery, reduces the incidence of RLNI, and improves both vocal and parathyroid function. It also attenuates inflammatory and stress responses, as indicated by changes in serum cytokines, thereby enhancing quality of life and patient satisfaction. This approach offers significant advantages for patients undergoing thyroidectomy for various thyroid disorders.